2018
DOI: 10.1103/physrevlett.121.126402
|View full text |Cite
|
Sign up to set email alerts
|

Fragile Topology and Wannier Obstructions

Abstract: Topological phases, such as Chern insulators, are defined in terms of additive indices that are stable against the addition of trivial degrees of freedom. Such topology presents an obstruction to any Wannier representation, namely, the representation of the electronic states in terms of symmetric, exponentially localized Wannier functions. Here, we address the converse question: Do obstructions to Wannier representation imply stable band topology? We answer this in the negative, pointing out that some bands ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
333
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(348 citation statements)
references
References 59 publications
(162 reference statements)
7
333
0
Order By: Relevance
“…The three remaining invariants completely fix 57 the Wilson loops in Eq. (21). Due to TRS they are necessarily even integers.…”
Section: Wilson-loop Invariantsmentioning
confidence: 99%
“…The three remaining invariants completely fix 57 the Wilson loops in Eq. (21). Due to TRS they are necessarily even integers.…”
Section: Wilson-loop Invariantsmentioning
confidence: 99%
“…Moreover, in contrast to the electronic quantum spin Hall systems, the photonic/acoustic quantum spin Hall systems feature fragile topology. In the literature, bands with fragile topology have gapless Wannier bands by themselves, but the Wannier bands can become gapped when a set of bands with gapped Wannier bands are added to the Wilson-loop calculation [77][78][79]. Indeed, when the first band is added to the Wilson-loop calculation (i.e.…”
Section: Quantum Spin Hall Effect and Fragile Topology In Photonic Anmentioning
confidence: 99%
“…Introduction.-Topological phases of matter, distinct from the conventional phases in that they are not characterized by the local order parameter but by the topological order parameter, have been one of the central topics of the condensed matter physics. Even ten years after the celebrated ten-fold-way classification [1][2][3] of the topological insulators/superconductors (TIs/TSCs) [4,5], the notion of topologically nontrivial states in non-interacting fermions has greatly extended its scope by incorporating the crystalline symmetries [6][7][8][9][10][11][12]. It was further revealed that short-range entangled quantum many-body states can also host topologically nontrivial state protected by symmetries, and they are now unified by the notion of symmetry protected topological phases (SPT phases) [13][14][15][16].…”
mentioning
confidence: 99%